(untitled) (Bangladesh Journal of Otorhinolaryngology, 2016)
Backround: Septoplasty in children is still a matter of debate, because it is thought that a surgical procedure on a developing structure might produce some adverse effects on normal nasal and facial growth.On the other hand septal deviation in children may alter the early physiological process of breathing, causing obligatory mouth breathing and consequently changing craniofacial development and even intellect. Objectives: The goal of this retrospective study is to indicate the importance of septoplasty in children,to evaluate the effects of paediatric nasal septal surgery on normal nasal and facial growth, improvement of symptoms and any complications of surgery. Methods: This is a retrospective study of 250 children in the age group of 7-14 years done at Maleka nursing Home , Bogra, Human care hospital, Rajshahi and Khidma hospital Dhaka,from January 1999 to December 2014.All patients were selected from history, clinical examination and selected investigations. All patients had X-ray soft tissue nasopharynx done to see adenoid enlargement.Some patients had done PTA and tympanometry to confirm OME. All patients had septoplasty done with left hemitranfixional incision with elevation of left mucoperichondrial flap and elevation of both mucoperiosteal flaps. In addition adenoidectomy was done for adenoid enlargement and myringotomy with grommet insertion for OME. Patients were followed up on day 8, day 15, 1 mothh, 6 month and one year after operation. Results: Out of 250 children there were 163 male(65.2%)and 87 female(34.8%).Age ranged from 7 to 14 years,lowest number of patients were between 7 and 8 years old-64(25.6%),between 9 and 11 years-73(29.2) and 113(45.2%) between 12 and 14 years.210 patients had septal deviation to left side(84%) Patient felt improvement in nose breathing in 85% of cases.The most often complication was nasal blockage due to insufficient removal of deviated septum in 9.2 % of cases.We had synechia in 8 cases and septal haematoma in 2 cases.There were no asthetic deformities. Conclusion: Effective septal correction by septoplasty in children not only relieves nasal blockage but also controls the associated symptoms.Septolasty in early childhood does not produce any untoward events in terms of the growth and development of the nose and face. Bangladesh J Otorhinolaryngol; October 2015; 21(2): 110-114